Evaluation of phakic intraocular lens power calculation using the new Linz-Homburg-Castrop formula and comparison with four conventional methods. Issue 2 (February 2023) - Wendelstein, Jascha A.; Hinterberger, Sarah; Hoffmann, Peter C.; Hirnschall, Nino; Koss, Michael J.; Langenbucher, Achim; Jirak, Paul; Bolz, Matthias
Abstract : We assessed the accuracy of phakic IOL power calculation methods in 91 eyes. The Olsen-Feingold formula provided significantly less eyes within a prediction error of ±1.0 D than all other formulas. Abstract : Purpose: To evaluate the accuracy of phakic intraocular lens (pIOL) power calculation in a middle European patient cohort. Setting: EyeLaser Clinic, Linz, Austria. Design: Single-center single-surgeon retrospective consecutive case series. Methods: Patients were included after uneventful pIOL surgery implanting 91 nontoric and toric Visian implantable collamer lens model V4c. Online Calculation and Ordering System (OCOS) software, JPhakic software, Olsen-Feingold formula, Holladay formula, and Linz-Homburg-Castrop (LHC) formula were compared. When possible, lens constants were optimized for the patient cohort. Data of single eye per patient were included. Outcome measures were mean absolute prediction error, median absolute prediction error, mean prediction error with SD, and median prediction error, as well as the percentage of eyes with an absolute prediction error within limits of 0.25 diopters (D), 0.5 D, 0.75 D, and 1.0 D. Results: 91 eyes of 91 patients were assessed. After application of the Cochran Q test, the Olsen-Feingold formula achieved a significantly lower percentage of eyes within an absolute prediction error of 1.0 D than all other methods. Conclusions: In the patient cohort, OCOS software, JPhakic software, and Holladay and LHC formulas showed equal results and can be cross-checked. The LHC formula was not published before. A ready-to-use Excel sheet is available as an addendum.